Dependência Química: avaliação das funções executivas, nível de fissura e estratégias de coping utilizadas por usuários de crack. - Costa, Sara Bahia (2020)
The disorder related to the use of psychoactive substances or chemical dependence generates devastating consequences in the lives of people who are affected by this problem, in addition to having a harmful impact on family members and society. Among the c